Pembuatan Glukosamin Hidroklorida dari Cangkang Udang dengan Energi Microwave - A. Zaeni; E. Safitri; I. N. Sudiana (Universitas Halu Oleo, 2017)
The application of microwave energy to processing glucosamine hydrochloride (GlcN-HCl) based chitosan white shrimp shell waste (Panaeus Merguensis) was investigated. Isolation and characterization of chitin and chitosan before GlcN-HCl hydrolysis were performed. Hydrolisis was using 2.45 GHz microwave energy. After that the GlcN-HCl was then characterized by using FTIR. Microwave has been used by varying the heating time of 3, 7, 11, and 15 minutes at the power of 450 W. The highest levels of GlcN-HCl obtained from the hydrolysis of chitosan using microwave at 11 minutes with a yield of 38.25%. GlcN-HCl which is generated showing the characteristics of GlcN-HCl hydrolysis completely soluble in water with the value of the melting point and spectrum 189,2°C. GlcN-HCl showed some functional groups are -OH groups, NH, NH3 + asymmetric, asymmetric CH3, CN and CO. The GlcN-HCl hydrolyzed by using the microwave is similar to that of hotplate one.